Correction: Razzaq et al. Development of Cephradine-Loaded Gelatin/Polyvinyl Alcohol Electrospun Nanofibers for Effective Diabetic Wound Healing: In-Vitro and In-Vivo Assessments. Pharmaceutics 2021, 13, 349 - Anam Razzaq; Zaheer Ullah Khan; Aasim Saeed; Kiramat Ali Shah; Naveed Ullah Khan; Bouzid Menaa; Haroon Iqbal; Farid Menaa (Pharmaceutics)
In the original publication [...]